Development of a Method for Increasing the Fire Resistance of Cast-iron Structures of Cultural Heritage Sites under Reconstruction - Sergey Puzach; Lisienkova Liubov; Ekaterina Кamchatova; Lyudmila Nosova; Viktoriya Degtyareva; Valentina Tarasova; Liudmila Komarova (Salehan Institute of Higher Education, 2024)
When reconstructing cultural heritage sites, significant changes to the original design planning are not allowed. More rational methods are needed to increase the fire resistance of historical buildings, which will ensure their fire safety and preserve their architectural value. Nowadays, most heritage sites do not meet the safety requirements of modern buildings. The purpose of the study is to develop a methodology for increasing the fire resistance of cast iron structures. The key tasks are increasing the fire resistance of buildings during reconstruction and ensuring their fire safety during operation. The tasks have been achieved by developing a new methodology for increasing the fire resistance of cast iron. It includes an integrated approach to assessing the risk of a fire, a predictive model for the occurrence of fire danger, as well as various scenarios for the fire development caused by cast iron heating. The results’ analysis has allowed us to determine the fire resistance limits of cast iron structures. The scientific novelty lies in the study of the fire resistance of cast iron structures using a three-dimensional mathematical model. The resulting values have been obtained via differential equations of the laws of mass conservation, momentum, gaseous energy, and the optical density of smoke. Doi: 10.28991/CEJ-2024-010-02-015 Full Text: PDF